2022
DOI: 10.1007/s10143-022-01794-4
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical selection of the ideal aneurysm clip by the use of a three-dimensional planning system

Abstract: Aneurysm occlusion rate after clipping is higher than after endovascular treatment. However, a certain percentage of incompletely clipped aneurysms remains. Presurgical selection of the proper aneurysm clips could potentially reduce the rate of incomplete clippings caused by inadequate clip geometry. The aim of the present study was to assess whether preoperative 3D image-based simulation allows for preoperative selection of a proper aneurysm clip for complete occlusion in individual cases. Patients harboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…VR systems do not have preservation problems, and they have been highly investigated for planning [ 43 - 45 ], focusing on force feedback, distance visualization, or a craniotomy approach [ 46 - 48 ]. Participants in VR studies could clip aneurysms multiple times, but training for the surgical experience was unrealistic although the simulation created an immersive environment.…”
Section: Discussionmentioning
confidence: 99%
“…VR systems do not have preservation problems, and they have been highly investigated for planning [ 43 - 45 ], focusing on force feedback, distance visualization, or a craniotomy approach [ 46 - 48 ]. Participants in VR studies could clip aneurysms multiple times, but training for the surgical experience was unrealistic although the simulation created an immersive environment.…”
Section: Discussionmentioning
confidence: 99%
“…Different assessment methods have been proposed to evaluate the impact of aneurysm simulators on both education and surgical planning. 12,34 A Japanese group presented a preclinical training program including two clipping sessions and an interim video review session, evaluated by an expert assessment based on Objective Structured Assessment of Technical Skills (OSATS). 29 Others have compared occlusion rates of novice versus experienced surgeons in preclinical settings.…”
Section: Objective Evaluation Of Our Simulator Training Programmentioning
confidence: 99%
“…In these cases, the rate of implant accordance, surgical complications, and procedural duration were reported to document trainees' performance. 30,34,41 Kimura et al proposed assessing the position of the clip and its neck coverage by an endoscope in the 3D-printed surgical situs. 41 Futami et al demonstrated the importance of CTA scans to assess aneurysm neck coverage after clipping as early as 2004.…”
Section: Simulator Training Improves Microsurgical Skills and Aneurys...mentioning
confidence: 99%
“…2a This concept is most apparent with the use of the VSP, which relies on data that can be obtained before treatment and provides helpful treatment information. While analogous work has been done with optimal clip placement based on preoperative imaging, 3a the major challenge with open surgery is not placing the clip, it is circumferential visualization of the aneurysm neck. Endovascular treatment is not limited by direct (or microscopic) visualization of the lesion, just radiographic imaging, which can be obtained prior to treatment.…”
Section: Commentsmentioning
confidence: 99%